2010
DOI: 10.2527/jas.2008-1674
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 12, 30, or 48 hours of road transport on the physiological and behavioral responses of sheep1

Abstract: To identify long-distance transport durations compatible with acceptable animal welfare, the aim of this study was to determine the responses of healthy sheep to road transport under good conditions for 12, 30, or 48 h. Merino ewes (n = 120; 46.9 +/- 0.39 kg) were allocated to road transport treatments of 12, 30, or 48 h, with 2 replicates per treatment. Blood and urine samples and BW were taken pretransport and at 0, 24, 48, and 72 h posttransport. Lying time was measured using data loggers. Increasing transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 19 publications
3
49
0
11
Order By: Relevance
“…In ewes, it has been reported that sheep which were transported for 30 and 48 hours, exhibit greater total plasma protein concentrations than those transported for 12 hours. Hp and albumin were considered within the total plasma protein levels (Fisher et al, 2010). More studies should be performed in this topic in order to assess the use of APPs as biomarkers of welfare in sheep and goats.…”
Section: Apps Of Importance In Small Ruminants Stress and Welfarementioning
confidence: 99%
“…In ewes, it has been reported that sheep which were transported for 30 and 48 hours, exhibit greater total plasma protein concentrations than those transported for 12 hours. Hp and albumin were considered within the total plasma protein levels (Fisher et al, 2010). More studies should be performed in this topic in order to assess the use of APPs as biomarkers of welfare in sheep and goats.…”
Section: Apps Of Importance In Small Ruminants Stress and Welfarementioning
confidence: 99%
“…Results revealed that the lambs transported for 3, 6 and 9 h lost more live weight than untransported lambs, the losses increasing with increasing journey duration. Fisher et al (2010) determined the responses of healthy sheep to road transport under good conditions for 12, 30 or 48 h without access to feed and water on board the vehicle. Increasing transport duration resulted in lower body weight and increased haemoconcentration at arrival, but these effects did not exceed clinically normal ranges for any transport duration, and sheep generally recovered to pre-transport values within 72 h of arrival.…”
Section: 33mentioning
confidence: 99%
“…são realizadas podem determinar o grau do estresse (Tarrant 1990, Fisher et al 2010. A perda de peso corporal, de acordo com a duração das jornadas, e seu efeito sobre as carcaças e carnes, são motivos de preocupação para a indústria e são constantemente investigados (Carter & Gallo 2008, Tadich et al 2009, Leme et al 2012.…”
unclassified
“…Variações relativas ao comportamento, às respostas dos sistemas nervoso autô-nomo, endocrinológico e imunológico são constantemente avaliadas com este objetivo (Hales & Brown 1974, Ferguson & Warner 2008, Cockram et al 2010, Fisher et al 2010.…”
unclassified